Substrates and temperatures in the germination of Eriotheca gracilipes seeds - Melo, Paulo Alexandre; Cavalcanti, Maria Idaline; Alves, Edna; Martins, Cibele; Araújo, Luciana (Revista Ciência Agronômica, 2016)
The Eriotheca gracilipes (K. Schum.) A. Robyns) is a forest specie that belongs to the Bombacaceae family and is considered an endemic specie from the Brazilian savanna. The aim of this study was to evaluate the best substrate and temperature for the vigor and germination test of E. gracilipes seeds. The experiment was carried out in a randomized design with a 4 x 7 factorial, with 28 treatments with the combination of four temperatures (20; 25; 30 and 20-30 °C) and seven substrates (coarse vermiculite, medium vermiculite, sand, Basaplant®, paper towel, on and between filter papers), with 4 repetitions of 25 seeds each. It was assessed germination, first count of germination, and germination speed index. In conclusion, for germination and vigor tests of Eriotheca gracilipes seeds it is recommended the paper roll as substrate at temperatures of 20-30, 25 or 30 °C, and the Basaplant® and paper roll at the temperature of 30 °C, respectively.